Characterisation and Classification of the Soils of Panchet Right Bank Sub-Catchments in the Upper Damodar Valley - Roy, B.D.; Bhattacharya, P.B.; Pandey, S.N. (Journal of Soil and Water Conservation, 2022)
Systematic Soil Survey of the Upper Damodar Valley, comprising an area of about 7000 sq. miles has been undertaken since 1960 with the object of recognising the different soils in the area and providing information on inherent soil characteristics and external land features as slope, depth and erosion condition of the different soils so as to classify and map these in terms of land use capability classes. This information is expected to serve as the basis for planning and execution of integrated soil conservation programme for the water- shed, which is expected to minimise quantity of silt load in the streams draining to the reservoirs and will improve the agricultural production and stand of forests of the area..